A escola ao longo da vida: trajetórias de mulheres da EJA da Escola Municipal Moysés Kalil - Elisângela Mara de Paula (2024)
The research presents a reflection on the trajectory of students of Youth and Adult Education (YAE) at Moysés Kalil Municipal School in Belo Horizonte. A class with unique characteristics that stands out mainly for being exclusively composed of women, mostly elderly, who resume their studies after retirement. For this, we draw on studies of YAE and issues of class, gender, and race from the concept of intersectionality. In this qualitative approach research, we used semi-structured interviews with five regular students of the class, seeking to understand the meanings of schooling throughout their lives, theoretically dialoguing with Freire (1996, 2000, 2005), Arroyo (2001, 2011, 2017), hooks (2006), Charlot (1996, 2020), and Ireland (2019). The results indicate that school reintegration, for these elderly students, signifies a transformation as women, subjects of their own choices, transforming the daily confrontation of inequalities with quality of life, recognizing themselves in spaces never before frequented, resignifying experiences and new possibilities. Education in the elderly phase of life emerges as a means of social inclusion after retirement. Our final product is the documentary: 60+? Present, which reveals the common trajectory of these students, translating reality through audiovisual means.